Diagnostic value of conventional MRI combined with DTI for neonatal hyperbilirubinemia - Ruifang Yan; Dongming Han; Jipeng Ren; Zhansheng Zhai; Fengmei Zhou; Jingliang Cheng (Elsevier, 2018)
Background: Neonatal hyperbilirubinemia (NHB) is a common clinical disease and can cause bilirubin encephalopathy in severe cases. It is now widely accepted that increased signal intensity in the globus pallidus on MR T1WI is an important sign of neonatal bilirubin encephalopathy. And brain diffusion tensor imaging (DTI) has not been used extensively to study hyperbilirubinemia (HB). So we compared newborns with different hyperbilirubinemia of different severities and healthy newborns in order to determine the relationships among MRI signal intensities, serum bilirubin levels, and the molecular changes in brain water diffusion in hyperbilirubinemia. Methods: Seventy-three newborns with hyperbilirubinemia were grouped into three groups: the mild increase group (M, 27 cases), the moderate increase group (O, 28 cases), and the severe group (S, 18 cases). The groups were based on serum bilirubin levels. We performed cranial MRI in these newborns, as well as 29 healthy full-term infants (group N). We compared and analyzed the mean signal values for the globus pallidus and the relationship between the bilirubin level and the score on the neonatal behavioral neurological assessment. Fifteen, 10, and 10 patients in groups M, O + S, and N were successfully examined using diffusion tensor imaging (DTI). We assessed the relationships among the signal from the globus pallidus, fractional anisotropy (FA), and average diffusion coefficient (DCav) of the posterior limb of the internal capsule (PLIC). Results: There were significant differences in the mean signal value of bilateral globus pallidus between group O/S and group N [p = 0.029 and 0.000 (left), 0.038 and 0.000 (right)]. There were no significant differences in bilateral FA or DCav values between the patient groups and group N. The bilateral PLIC-FA and DCav values were significantly different between the patient groups and group N (P = 0.014 and 0.047, respectively). Conclusions: Increased signal intensity in the globus pallidus on T1-weighted imaging can be used as an objective index to evaluate neonatal bilirubin encephalopathy. Globus pallidus and PLIC injuries are likely to occur when the total serum bilirubin level is ≥20 mg/dl. Key Words: neonates, neonatal hyperbilirubinemia, neonatal bilirubin encephalopathy, MRI, diffusion tensor imaging (DTI)